On a related Thompson problem in $\mathbb{R}^k$ - Agama, Theophilus (My University, 2022)
In this paper we study the global electrostatic energy behaviour of mutually repelling charged electrons on the surface of a unit-radius sphere. #find attached file for the complete abstract
Keywords: electrostatic energy; Coulomb; electrons; minimal